(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
The right to a speedy trial is a cornerstone of criminal justice systems, ensuring that justice is delivered without undue delay and safeguarding the rights of the accused and victims alike. In both India and the United States, this right has evolved through constitutional provisions, judicial interpretations, and legislative frameworks. However, systemic delays, procedural inefficiencies, and institutional limitations have hindered its effective realization. This article undertakes a comparative study of speedy trial mechanisms in India and the United States, analysing their constitutional foundations, statutory frameworks, judicial approaches, and reform initiatives. While India recognizes the right to a speedy trial as an integral component of the right to life and personal liberty under Article 21, the United States explicitly guarantees it under the Sixth Amendment, supported by the Speedy Trial Act of 1974. The study highlights key challenges such as case backlog, undertrial detention, and procedural delays, and evaluates reform measures including case management systems, fast-track courts, and digital justice initiatives. The comparative analysis reveals that while the United States has a more structured statutory framework, India has relied heavily on judicial activism to enforce this right. The article concludes by suggesting comprehensive reforms aimed at strengthening institutional capacity, enhancing technological integration, and ensuring effective implementation of speedy trial guarantees in both jurisdictions.